RI 9440 - Underground Test Results of a Laser-Based Tram Control System for a Continuous Miner - Donna lynne Anderson (The National Institute for Occupational Safety and Health (NIOSH), 1992)
This report documents the status of a laser-based underground guidance system for tracking and controlling the movements of underground mobile mining equipment. This research is part of a multiple project effort at the U.S. Bureau of Mines to increase mine safety and efficiency by developing technology for computer-assisted mining. Guidance systems, which can track and control the movements of underground mining equipment, are essential during computer-assisted mining operations. A continuous mining machine at the Bureau's surface test facility served as the test-bed for initial development and experimentation of this guidance system. Subsequently, a continuous mining machine in an underground mine served as the platform for in-mine experimentation The first section of this report includes details of the laser sensors, communication network, and computer hardware. The next section includes experimental results, which show the system capable of accurately tracking and controlling the tram maneuvers of a continuous miner underground. The final section discusses conclusions and recommendations.